Internalisasi Nilai-Nilai Ahlusunnah Wal Jama’ah An-Nahdliyah dalam Pembelajaran Aswaja Kelas VIII MTs Ungguln Al-Mu’ayyad Gumirih-Singojuruh Tahun Pelajaran 2020/2021 - Ahmad Izza Muttaqin; Irfan Afandi; Nike Putri Wulandari (An Nahdhoh Jurnal Kajian Islam Aswaja, 2021)
The internalization of the values of Ahlusunnah wal jama'ah an-Nahdliyah used in the VIII grade Aswaja learning at MTs Unggulan Al-Mu'ayyad Gumirih-Singojuruh is the value of tawasuth, I'tidal, tawasuth, tawazun. This study uses descriptive qualitative and in the process of collecting data using non-participant observation methods, semi-structured interviews, and documentation. The research subjects in this study were Aswaja class VIII teachers and class VIII students. The validity of the data is done by triangulation of sources, and for data analysis includes data collection, data reduction, data display, conclusion drawing/verification. The results of this study explain that the VIII grade Aswaja teacher at MTs Unggulan Al-Mu'ayyad Gumirih-Singojuruh in internalizing the values of Ahlusunnah wal jama'ah an-Nahdliyah in Aswaja learning uses planting, habituation and exemplary and the supporting factors are Madrasas are in the environment. Islamic boarding schools, many educators come from Islamic boarding schools and understand the teachings of Aswaja an-Nahdliyah. Meanwhile, the inhibiting factor is that in the worksheets students still use intellectual languages, causing students at this MTs age to be confused in understanding the language, students at this age are still said to be of the age to like fairy tales and play in general and focus on paying attention to educators explaining only ten minutes and it's been said well by educators